Scope of pediatric neurosurgery unit in a neurosurgical referral center of a low-income country: survey of caseload and “take-home” actions provided by rotation at United States pediatric hospital - Koirala, Sagar; Koirala, Sharad; Smith, Edward (Nepal Journal of Neuroscience, 2026)
Introduction: Nepal’s population is 30 million, and 28% are under the age of 14. There are only 116 neurosurgeons, with none specifically committed to pediatric neurosurgical practice, nor is there a dedicated pediatric neurosurgery center. Consequently, there is an immediate need for developing pediatric neurosurgery practices, requiring analysis of the most prevalent neurosurgical disorders endemic to Nepal to identify areas of treatment focus, in addition to training for pediatric neurosurgical subspecialists. In response to these needs, we present our initial experience surveying the current pediatric neurosurgical caseload at the tertiary referral center in Nepal and summarize key learning points derived from a visiting rotation at a high-volume United States (US) pediatric neurosurgical practice. Materials and Methods: Retrospective case analysis at a tertiary level neurosurgical referral center in Nepal; all operative cases 18 years of age or younger over a 5-year period were included, categorized by pathology and treatment. Following this, a three-month rotation at Boston Children’s Hospital (BCH) was subsequently reviewed to identify key learning points relevant to impacting practice upon return to Nepal. Result: There were 601 cases performed during the 5-year period. Male to female ratio was 2:1. Common operative cases included trauma, hydrocephalus, tumors, brain abscesses, vascular malformations, craniovertebral junction anomalies, spinal dysraphism and seizure. With a focus on these conditions, rotation lessons from BCH were identified to improve treatment of these specific conditions in Nepal, with major learnings in operative efficiencies and resource allocation. The learning was applied to make changes in practice in the hospital. Conclusion: This work provides a current review of pediatric neurosurgery in Nepal and has highlighted the common neurosurgical treatments provided. These data will direct future areas of focus for training and resource allocation for planning a dedicated unit in Nepal. In addition, the experience at the US teaching hospital has led to the development of novel treatment strategies upon return to Nepal.